RANCANG BANGUN APLIKASI WORKFLOW PELAPORAN PEMAKAIAN SPARE PART KAPAL BERBASIS WEB PADA PT. RUKINA SUKSES ABADI - Pebriantono, Pebriantono; Nurcahyawati, Vivine; Erstiawan, Martinus Sony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Logistic department is one department at PT . Rukina Sukses Abadi that supports the company's operations by managing the spare parts ship and one of the outputs of this department is reporting procurement of spare parts . As part of the logistic department late in making statements procurement of spare parts and long reports to the purchasing section , it can hinder the performance of the ship because the ship will wait for a new spare part is needed , so the company could suffer losses owing to ships that do not work.Based on these issues , then the author made application workflow reporting the use of spare parts web-based, in this system there is a list of input request , form input data usage and features of data management usage and online demand spare parts can be giving notifications when usage and the demand for spare parts , so as to overcome the problem of the length of an agreement that could hamper the activities of dredgers.Conclusion The results of trials that have been conducted , application usage reporting workflow spare parts can perform user management and request spare parts directly when the ship parts to wear or ask for spare parts , and is able to generate reports when the procurement of spare parts as well.